Hadith #2376 - Sunan Abi Dawud - Abdur Rahman bin al-N'man عبد الرحمن بن النعمان بن معبد بن هوذة; Abu Ja'far al-Nafaili عبد الله بن محمد أبو جعفر النفيلي الحران; Ali bin Thabit al-Jzry علي بن ثابت الجزري أبو أحمد (Sunan Abi Dawud)
The Messenger of Allah (ﷺ) said: Neither vomiting, nor emission, nor cupping breaks the fast of the one who is fasting.
Grade: Da'if